An Analysis of Trading Behaviour of Foreign and Domestic Institutional Investors in the Indian Stock Market : An Empirical Study - Sathish, P. (Indian Journal of Research in Capital Markets, 2020)
India is an attractive investment destination for foreign portfolio investors in order to earn higher returns and risk diversification. FPI investments have predominantly been increasing in the Indian stock market since 1992. In the past two years, domestic institutions have been strong players in the Indian equity markets. The systematic monthly inflows into mutual funds have been impressive, and hence, they have a lot of surplus cash to accumulate some good-quality stocks. This buying by DIIs has saved the market from steep falls during the periods when FIIs resorted to basket-selling. Hence, investment patterns and the behaviour of FPIs and DIIs are dissimilar in the Indian stock market. There is a need to study the presence of feedback trading and causality between institutional investments (FPIs and DIIs) in the Indian stock market. To analyze this, the study took 2440 daily observations (short run) from April 1, 2007 to November 31, 2017 and 128 monthly observations (long run) from April 30, 2007 to November 30, 2017. The total reference period for this study is 10 years and 8 months. The study applied Granger causality test and vector autoregressive model to check the causality and presence of feedback trading between the institutional investments and Nifty returns. The study found that FPIs are positive feedback traders, while DIIs are negative feedback traders in the short run. However, the feedback trading does not exist in the long run. Also, the study proved the existence of bidirectional causality between the institutional investments and the Indian stock market in the short run.